Integrated Uncertainty Management and Applications - Huynh, Van-Nam; Nakamori, Yoshiteru; Lawry, Jonathan; Inuiguchi, Masahiro (Advances in Intelligent and Soft Computing, 2010)
Solving practical problems often requires the integration of information and knowledge from many different sources, taking into account uncertainty and impreciseness. Typical situations are, for instance, when we need to simultaneously process both measurement data and expert knowledge, where the former may be uncertain and inaccurate due to randomness or error in measurements whilst the latter are often vague and imprecise due to a lack of information or human's subjective judgements. This gives rise to the demand for methods and techniques of managing and integrating various types of uncertainty within a coherent framework, so as to ultimately improve the solution to any such complex problem in practice. The 2010 International Symposium on Integrated Uncertainty Management and Applications (IUM'2010), which takes place at the Japan Advanced Institute of Science and Technology (JAIST), Ishikawa, Japan, between 9th-11thApril, is therefore conceived as a forum for the discussion and exchange of research results, ideas for and experience of application among researchers and practitioners involved with all aspects of uncertainty modelling and management.